Herbivory by Atta vollenweideri: Reviewing the significance of grass-cutting ants as a pest of livestock - Sabattini, Julian; Bollazzi, Martin (Frontiers in Insect Science, 2023)
The grass-cutting ant Atta vollenweideri is well suited to study the negative effect leaf-cutting ants have on livestock production in South American grasslands because they forage on the same plants as cattle. This work studied the impact of Atta vollenweideri on livestock production in Argentinean rangelands. First, we assessed A. vollenweideri herbivory rates and its economic injury level (EIL). Second, working with satellite imagery in a region covering 15000 ha, we estimated the percentage of this area that surpassed the calculated EIL. Results show that A. vollenweideri consumed approximately 276 kg dry plant weight/ha/year, with grasses being the most foraged (70%). Ants also cut 25% of herbs and 5% of trees. In summer and autumn, ants consume more grasses, while in winter and spring, herbs and trees are also significantly cut. Ants consumed 7% of the forage demand needed to raise a calf according to the management regime applied by farmers. Our calculated EIL (5.85 nests/ha) falls in the range of previous works. Colonies are absent in 93.6% of the surveyed area, while their density is below the EIL in 6.2%. A. vollenweideri populations surpassed the EIL in only 0.2% of the area, which corresponds to 2.6% of the locations holding colonies. These results question the perception that Atta leaf-cutting ants are a pest for livestock production. Although ants consume a small percentage of cattle’s forage demand, evidence that ants and cattle are competing in the few cases that density surpasses the EIL is arguable. First, grass-cutting ants are capable of consuming herbs and trees other than the grasses on which cattle mostly feed. Second, there is no evidence indicating that both are cutting the same plant portions when preferences overlap. Third, evidence suggests that ants are not displaced under high-pressure grazing regimes by cattle. In the countries where A. vollenweideri is present, decision makers had promulgated several acts making its control mandatory. It is time to revisit the pest status of A. vollenweideri and include the use of EIL as a control criterion.